The Psychology of Faith and Religious Identity: How Theology Shapes Worldview and Self-Perception - Andrei Efremov (Pharos Journal of Theology)
The purpose of this study was to examine the role of religious identity and theological beliefs in shaping individuals’ perceptions of the world and themselves, as well as their influence on social adaptation in the United States. The methodology employed included surveys, statistical analysis, and PESTEL analysis. Additionally, a mechanism was developed to assess the impact of religious practices on individuals’ worldview and their adaptation to the social environment. The findings indicate that religion significantly influences respondents’ perceptions of the world and their moral beliefs. The majority of respondents identified as Christians, highlighting the importance of Christian values in shaping their views. Specifically, 60% of respondents identified as Christians, while 15% considered themselves atheists. Furthermore, 35% stated that their moral beliefs were entirely shaped by religious teachings, and 50% reported that religion enabled them cope with stress through prayer or meditation. Religious practices, such as prayer and meditation, were found to actively assist individuals in managing stress and navigating life’s challenges. A significant proportion of respondents noted that religion influenced their perspectives on social and political issues, though for some, religion was not the primary determinant of their beliefs. Overall, the study demonstrated that while religion plays a role in shaping attitudes towards social and political matters, the religious beliefs of most respondents remained stable over time.